Granulometric profile of corn silage produced in rural properties of Triângulo Mineiro (Research, Society and Development, 2024)
Properly chopping corn for silage production is essential to improve starch digestibility through uniform grain breakdown, facilitating the action of digestive enzymes in animals. This process not only increases the availability of nutrients such as starch and proteins, but also contributes to preserving the nutritional quality of the silage during storage. The objective of this work was to investigate the granulometric profile of corn silage in rural properties located in the Triângulo Mineiro region, state of Minas Gerais (MG), Brazil, that is, samples were collected from 19 rural producers in order to quantify and characterize their granulometry, according to the methodology of KPS (Kernel Processing Score) analysis, as well as the amount of grain that underwent mechanical processes, in order to verify the digestive and nutritional standard of dairy cows in production, and consequently, the technological level of dairy producers in the region. The analyzes were carried out in the laboratory of the Federal Institute of Triângulo Mineiro – Uberlândia campus, where it can be seen that 63% of the properties obtained excellent processing of corn silage, 21% presented adequate processing and only 16% of these were classified as having poor processing, demonstrating the need to carry out more frequent assessments and improvements to ensilage processes to ensure a more consistent quality of corn silage, which will not only benefit the ingestion and digestion capacity of cattle, but will also contribute to the conservation and overall effectiveness of silage in rural properties.